Implementing Positive Behavior Support in Preschools: An Exploratory Study of CW-FIT Tier 1. (January 2017) - Jolstead, Krystine A.; Caldarella, Paul; Hansen, Blake; Korth, Byran B.; Williams, Leslie; Kamps, Debra
Challenging behavior in preschool is a serious concern for teachers. Positive behavior interventions and supports (PBIS) have been shown to be effective in reducing such behaviors. Class-Wide Function-Related Intervention Teams (CW-FIT) is a specific multi-tiered intervention for implementing effective classroom management strategies using PBIS practices. CW-FIT has been shown to be effective in elementary classrooms but has not yet been evaluated with younger age groups. CW-FIT Tier 1 is a group contingency utilizing social skills training, teacher praise, and positive reinforcement to improve student behavior. The present study examined the effects of CW-FIT Tier 1 implementation on student group on-task behavior and on teacher praise and reprimand rates in four preschool classrooms. A single-subject delayed multiple baseline design with embedded reversals was used to evaluate impact. Results indicated the intervention increased student group on-task behavior and teacher praise to reprimand ratios. Both teachers and children found CW-FIT Tier 1 to be socially valid. Limitations and implications of this study for researchers and practitioners are discussed.